Grain size, morphometry and mineralogy of airborne input in the Canary basin : evidence of iron particle retention in the mixed layer (2016)
SUMMARY: Aeolian dust plays an important role in climate and ocean processes. Particularly, Saharan dust deposition is of importance in the Canary Current due to its content of iron minerals, which are fertilizers of the ocean. In this work, dust particles are characterized mainly by granulometry, morphometry and mineralogy, using image processing and scanning northern Mauritania and the Western Sahara. The concentration of terrigenous material was measured in three environments: the atmosphere (300 m above sea level), the mixed layer at 10 m depth, and 150 m depth. Samples were collected before and during the dust events, thus allowing the effect of Saharan dust inputs in the water column to be assessed. The dominant grain size was coarse silt. Dominant minerals were iron oxy-hydroxides, silicates and Ca-Mg carbonates. A relative increase of iron mineral particles (hematite and goethite) was detected in the mixed layer, reflecting a higher permanence of iron in the water column despite the greater relative density of these minerals in comparison with the other minerals. This higher iron particle permanence does not appear to be explained by physical processes. The retention of this metal by colloids or microorganisms is suggested to explain its long residence time in the mixed layer.